2013
DOI: 10.1097/prs.0b013e3182a00e79
|View full text |Cite
|
Sign up to set email alerts
|

Buried Flap Reconstruction after Nipple-Sparing Mastectomy

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The introduction of skin-sparing and nipple-sparing mastectomy has allowed immediate breast reconstruction to gain momentum [27]. Here, the native breast skin envelope remains intact, which facilitates good aesthetic results, especially for microvascular autologous tissue-based reconstructions [28][29][30]. Psychologically, patients receiving IBR show less anxiety or depression and higher levels of self-esteem, sexuality and an increased quality of life [4,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of skin-sparing and nipple-sparing mastectomy has allowed immediate breast reconstruction to gain momentum [27]. Here, the native breast skin envelope remains intact, which facilitates good aesthetic results, especially for microvascular autologous tissue-based reconstructions [28][29][30]. Psychologically, patients receiving IBR show less anxiety or depression and higher levels of self-esteem, sexuality and an increased quality of life [4,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported infection rates of 1.5% to 17.8% 14–16,18 after NSM with tissue expander placement, and implant loss rates as high as 9.9% 14 . Breast infection rates ranging from 1.9% to 7.4% have been reported after autologous reconstruction 12,19 . One prior study found increased rates of infections requiring PO antibiotics with immediate tissue expander reconstruction compared with immediate autologous reconstruction, but this prior study did not find increased rates of infections requiring IV antibiotics with tissue expander reconstruction 12 .…”
Section: Discussionmentioning
confidence: 92%
“…As we previously advocated that surgical treatment of breast cancer has entered a scarless era, efforts were made in forgoing the skin paddles during ms-TRAM/DIEP breast reconstruction, so as to minimize the surgical scar and improve the cosmetic outcome [9]. Levine et al reported that placing an implantable doppler around the site of anastomosis was su cient for post-operative surveillance of the buried DIEP ap and forgoing of the skin paddles was feasible [10]. However, the implantable doppler was not easily accessible.…”
Section: Introductionmentioning
confidence: 99%